1999
DOI: 10.1002/(sici)1097-0193(1999)8:4<209::aid-hbm5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortical networks subserving pursuit and saccadic eye movements in humans: An FMRI study

Abstract: High-field (3 Tesla) functional magnetic resonance imaging (MRI) was used to investigate the cortical circuitry subserving pursuit tracking in humans and compare it to that for saccadic eye movements. Pursuit performance, relative to visual fixation, elicited activation in three areas known to contribute to eye movements in humans and in nonhuman primates: the frontal eye field, supplementary eye field, and intraparietal sulcus. It also activated three medial regions not previously identified in human neuroima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
152
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(185 citation statements)
references
References 79 publications
25
152
0
1
Order By: Relevance
“…Gottlieb et al 1993;Gottlieb and Goldberg, 1999;Schlag-Rey et al 1997;Schlack et al 2003;Tian & Lynch, 1995). These are two frontal areas, the supplementary eye fields (SEF) and the frontal eye fields (FEF), and the posterior parietal cortex (PPC) (Berman et al 1999;Petit and Haxby 1999;O'Driscoll et al 1998). In our study, the cortical area associated with antisaccade performance was in the right superior frontal cortex within Brodmann's area 6.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Gottlieb et al 1993;Gottlieb and Goldberg, 1999;Schlag-Rey et al 1997;Schlack et al 2003;Tian & Lynch, 1995). These are two frontal areas, the supplementary eye fields (SEF) and the frontal eye fields (FEF), and the posterior parietal cortex (PPC) (Berman et al 1999;Petit and Haxby 1999;O'Driscoll et al 1998). In our study, the cortical area associated with antisaccade performance was in the right superior frontal cortex within Brodmann's area 6.…”
Section: Discussionmentioning
confidence: 50%
“…There was no overlap between this area and that related to antisaccade errors. However, activation studies show that although saccades and smooth pursuit activate the same oculomotor regions, the areas mediating saccades and pursuit are actually distinct and are located in near-by but different areas (Berman et al 1999, Petit andHaxby, 1999;Rosano et al 2002). Berman et al (1999 demonstrated that smooth pursuit and saccades activated the anterior and posterior cingulate cortex with the spatial extent being greater for pursuit in the posterior cingulate, which may have a role in integrating sensory and motor signals, which is especially important for sustained pursuit performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any signiWcant activation in the SEF during saccadic eye movements. Activation in the SEF related to reXexive or voluntary saccade eye movements has been reported by some (Fox et al 1985;Darby et al 1996;Petit et al 1996;Law et al 1998;Luna et al 1998;Muri et al 1998;Berman et al 1999;Nobre et al 2000), but not by others (Anderson et al 1994;Mort et al 2003).…”
Section: Discussionmentioning
confidence: 94%
“…PET studies have shown activation during reXexive saccades in FEF (Anderson et al 1994;Sweeney et al 1996), PEF (Anderson et al 1994), cerebellum, striate cortex and posterior temporal cortex (Sweeney et al 1996). fMRI studies have also shown activation in FEF (Petit et al 1997;Luna et al 1998;Muri et al 1998; Berman et al Table 2 Areas of activation (voluntary saccades > Wxation) with cluster size, maximum t value within the cluster, MNI coordinates of the maximum t value, anatomic labels, percentage of cluster size and functional area All areas were thresholded at P < 0.05 with FDR (whole brain study) or at cluster level (P < 0.05) corrected for multiple comparisons (cerebellum study) and with a minimum cluster size of 10 voxels L left hemisphere, R right hemisphere, FEF frontal eye Welds, PEF parietal eye Welds, MT/V5 motion-sensitive area (MT/V5), PVA/V1 primary visual areas (V1) a The unassigned areas for each cluster are not listed in the Muri et al 1998;Berman et al 1999;Nobre et al 2000), and the cerebellum (Nobre et al 2000), as well as in SEF (Luna et al 1998;Berman et al 1999), the precuneus , the cingulate gyrus Nobre et al 2000), MT/V5, PVA/V1 and the midbrain. In general, subjects in these studies were asked to execute saccadic eye movement towards suddenly appearing peripheral targets.…”
Section: Discussionmentioning
confidence: 99%